The Influence Of Sociodemographic Factors On The Success Of Exclusive Breastfeeding: A Narrative Review - Qomariah Dianti Sari (Sean Institute, 2024)
Exclusive breastfeeding is the best primary food for infants and lasts for 6 months. However, the practice of exclusive breastfeeding is often influenced by social, economic, and environmental factors, resulting in poor practices. This study aims to analyze the influence of sociodemographic factors on the success of exclusive breastfeeding. The research method used in this study is a literature review with the type is narrative review. The article search process in this study used the keywords